EVALUASI TINGKAT PENERIMAAN DAN PENGGUNAAN SISTEM SMARTSCHOOL SEBAGAI MEDIA PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 MENGGUNAKAN UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) MODEL(STUDI KASUS : SMAN 96 JAKARTA) - Siti Khofiah Munjiyanti (2022)
In order to provide support facilities for distance learning activities, SMAN 96 Jakarta cooperates with an e-learning service provider, named Smartschool. Use of e-learning during the COVID-19 pandemic can assist organization in managing all distance learning activities such as exams and assignment collection. However, to create benefits from using the system, the system must first be accepted and used properly by its users. For this reason, the purpose of this research is to examine user acceptance of the use of Smartschool e-learning by using one of the user acceptance models, named the Unified Theory of Acceptance and Use of Technology (UTAUT) with data analysis method is Partial Least Square - Structural Equation Modeling (PLS-SEM). This research was conducted using quantitative methods by distributing questionnaires to 271 students of SMAN 96 Jakarta. Based on the results of the research hypothesis test, it can be seen that the UTAUT model can explain 57.8% of the variance in the intention to use e-learning Smartschool and 52.1% variance in the behavior of using e-learning Smartschool with four variables that influence it, named performance expectancy, effort expectancy, social influence and facilitating conditions and there are no moderating variables of gender, experience and voluntariness of use that are proven to affect the level of acceptance and use of Smartschool e-learning.